Quotations for the extra works listed in the letter BRACU-NCP/2019/89A, dated 06th August 2019 - Brac University (Brac University, 2023)
This record consists of general correspondence regarding quotations for the extra works listed in the letter BRACU-NCP/2019/89A, dated 06th August 2019 of BRAC University new campus project.